Medical students’ perceptions on the adequacy and effectiveness of pharmacology teaching during preclinical years - Norazlina Mohamed; Siti Mariam Bujang; Mohamad-Sharif MA; Norain MM; Muhammad-Adam AC; Hazlinda M; Darishini G (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Pharmacology teaching during preclinical years is important for medical students to make rational choices in choosing suitable treatment for patients in future. Therefore, the present study determined the adequacy and effectiveness of pharmacology teaching in the undergraduate medical program at the Universiti Kebangsaan Malaysia Medical Center (UKMMC). Suggestions for improvement of the curriculum were also identified. An online questionnaire on the perceptions of pharmacology teaching methodology was distributed to a total of 459 medical students in 4th and 5th year at UKMMC. The questionnaire covered demographics, perceptions about pharmacology teaching, the ideal teaching learning methodology for learning pharmacology, pharmacology topics which are useful for future clinical practice, the pharmacology topic which was most interesting and recommendations for improvement. The response rate was 46.4% and majority of the participants were females (65.7%). Most of the students agreed that interactive learning was more helpful than didactic lectures (88.0%). Seventy percent of the students reported that pharmacology lectures in the preclinical years were helpful during the clinical years. Percentage of students who agreed that pharmacology teaching in their preclinical was adequate for their clinical practice was 47.0%. There was no association between demographic variables (gender, race, year of study and medical family background) and interest in pharmacology (p>0.05). In conclusion, the pharmacology teaching during preclinical years was perceived to be effective and useful for students’ clinical practice. More pharmacology teaching sessions in clinical years was suggested which may improve adequacy of pharmacology teaching.